Estimating the Concentration of Some Heavy Metals (Cadmium and Nickel) in Blood Serum Samples of Lung Cancer Patients in Iraq - Haneen Waheed Kadhim; Heiyam Najy Hady (Genius Journals, 2023)
Through the study, which took into account 20 samples of healthy blood serum among males and females and 50 samples of blood serum from cancer patients lung also among males and females, the concentrations of Cadmium and Nickel levels were studied in parts per billion units where the marginal concentrations were high for healthy males and females. Unlike Nickel, this study supports the hypothesis that the exposure of Cadmium and Nickel increases lung cancer risk. These findings can accelerate the diagnosis and treatment of Lung cancer .There is a need to conduct more studies and research with more samples to determine whether the heavy metals have a role in causing the lung cancer.
Keywords: Lung cancer; blood serum sample; SPSS Program; spectroscopy